Stability and Antimicrobial Studies of Mixed Ligand Complexes of Nickel(II) with SomeReactive Methylene Compounds and Carboxylic Acid - Ambwani, Jitendra; Taneja, Ajay (Asian Journal of Chemistry, 2010)
The stability of simple and mixed complexes of Ni(II) with oxalic acid (Ox2–), N-(2-ethoxy) phenyl malonamic acid (EPM–) and N-(4-methyl) phenyl malonamic acid (MPM–) have been studied polarographically. Lingane's method DeFord and Hume's method have been used to determine the composition and stability constants of simple complexes and Schaap and McMaster's method for the mixed systems in aqueous media. Antimicrobial studies of ligands and their simple and mixed metal complexes were carried out by screening them in vitro against bacterial species Escherichia coli (gram -ve) and Staphylococcus aureus (gram +ve).